PRACTICAL COUGH EXERCISES IN CHILDREN WITH INEFFECTIVE AIRWAY CLEARANCE PROBLEMS DUE TO BRONCHPNEUMONIA AT DUSTIRA TK II CIMAHI HOSPITAL: CASE REPORT - Wulandari, Sri; Nur Insani, Tiara (JURNAL KESEHATAN KARTIKA, 2024)
B Background: Babies and children are susceptible to bronchopneumonia due to infection caused by Streptococcus pneumonia and Haemophilus influenzae. Nursing problems that often arise due to bronchopneumonia are ineffective airway clearance due to airway hypersecretion and the child's inability to expel secretions. One of the non-pharmacological therapies to overcome this problem is effective cough training. Objective: Effective cough training aims to train children who cannot yet cough effectively to be able to clear the larynx, trachea, and bronchioles of secretions or foreign objects in the airway. Method: This case report describes the application of effective cough training in a child aged 7 years 11 months with ineffective airway clearance problems. Sampling was based on the criteria of the child's age being over 5 years, rapid breathing frequency, and the presence of additional breath sounds on lung auscultation. Results: The results of applying effective coughing training for 3 days showed changes in the child's general conditions, phlegm was able to come out, there wasn't additional breath sound (rhonchi), and respiratory frequency and oxygen saturation improved. Conclusion: The conclusion is that this intervention can help children expel phlegm, improve respiratory frequency, and increase oxygen saturation. Suggestions for pediatric nurses, that effective cough training can be an independent intervention in overcoming problems with respiratory system disorders.